Proceedings of the Ocean Drilling Program, 148 Scientific Results 1996
DOI: 10.2973/odp.proc.sr.148.101.1996
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Lavas from Hole 896A

Abstract: Hole 896A is a second deep basement hole within oceanic crust formed at the Costa Rica Rift, which penetrated ~290 m of the lava sequence. The lava sequence is dominated by pillow lavas and massive flows, although minor breccias and two thin dikes were also recovered. The basalts are predominantly plagioclase + olivine phyric tholeiites, although in one section of the hole (353.1-392.1 mbsf) clinopyroxene is also present as phenocrysts.Geochemically, the basalts are strongly depleted, moderately evolved mid-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Potassium content is also lower in lava flows than in pillow basalts. The only exception is Hole 896A, where extensive alteration along rims of lava flows was observed, possibly caused by focusing of fluid flow along lava flow contacts [ Alt et al , 1993; Brewer et al , 1996]. …”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Potassium content is also lower in lava flows than in pillow basalts. The only exception is Hole 896A, where extensive alteration along rims of lava flows was observed, possibly caused by focusing of fluid flow along lava flow contacts [ Alt et al , 1993; Brewer et al , 1996]. …”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…We have shown that the Bluff Complex is geochemically distinct from the bulk of the BST. With the exception of the relative enrichments in Ba, Sr, and Pb, the Bluff samples closely resemble ultradepleted basalts (D-MORB) recovered from ocean-floor drilling on the East Pacific Rise (Marsh et al 1983;Brewer et al 1996). Genesis involving a subduction fluid component is invoked to account for the Ba, Pb, and Sr anomalies, but the lack of enrichment in other fluid-mobile elements (K, U, Rb) confirms that these basalts are not typical arc rocks (Pearce & Peate 1995).…”
Section: Genesis Of the Igneous Rocks Of The Brook Street Terranementioning
confidence: 88%
“…Both whole‐rock and glass data have been analyzed from Hole 896A by the shipboard scientific party [ Alt et al , 1993; Brewer et al , 1996] and Fisk et al [1996], respectively. The whole‐rock chemistry was analyzed by X‐ray fluorescence spectrometry [ Brewer et al , 1996], and the glass data were analyzed by electron microprobe [ Fisk et al , 1996]. …”
Section: Geological Backgroundmentioning
confidence: 99%
“… Brewer et al [1996] identified five chemical units in the Hole 896A core (refer to Figure 11). (1) Unit A extends from 195.1 to 340 mbsf, and basalt samples have relatively uniform compositions.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation